(untitled) (Asian Journal of Ethnobiology, 2022)
Abstract. Puryanti, Hermanu J, Wahyuni S. 2019. Study of Javanese philosophical values ??in Kliwonan batik from Sragen District, Central Java, Indonesia. Asian J Ethnobiol 2: 51-69. The research objectives are to describe: (i) The background of Kliwonan batik in Sragen District. (ii) The history of creating the Kliwonan batik motif in Sragen District. (iii) Javanese philosophical values ??contained in Kliwonan batik in Sragen District. This research was conducted in Kliwonan Village, Masaran Sub-district, Sragen District, Central Java, Indonesia. This study used the descriptive qualitative method. The sample used is purposive sampling. Meanwhile, interview, observation, and document analysis used the data collection technique. The validity of the data used is a triangulation technique, namely triangulation of data sources and triangulation of methods. The data analysis technique in this study used a qualitative analysis model and interactive analysis. Based on the results of this study, conclusions can be drawn: (i) Kliwonan batik craft in Kliwonan Village is related to Ki Ageng Butuh. For the services of Ki Ageng Butuh, finally, the village of Kuyang (Koni Kliwonan) and the village of Butuh (now the village of Gedongan), which are separated by the Bangawan Solo river, are used as bounty villages, so in this village, the palace culture also developed, namely batik, starting from the Abdi dalem kriya who become a batik worker in the palace. These skills were then developed in the village of Butuh-Kuyang and passed down from generation to generation in the Butuh and Kuyang areas which the Bengawan Solo River only limits. (ii) The process of creating batik motifs includes several aspects until the creation of a motif: function, material, form, technique or process, and aesthetics. All of these aspects start with an idea. In traditional written batik in Kliwonan, the idea of ??making motifs is influenced by external factors in the form of cultural factors. Traditional batik motifs are designed based on traditions passed down from generation to generation as a form of cultural preservation and to fulfill requests related to traditional needs. So in traditional batik motifs and visual beauty, there is also meaning. The internal aspects of making traditional batik motifs and new creations are the same, but different creative ideas affect the overall visual form. (iii) Kliwonan batik is part of Surakarta batik, so the motifs in batik are also full of Javanese philosophical values. The traditional written batik motifs in Kliwonan Village consist of: (a) The semen motif is a classic batik of Semen Surakarta, which is full of symbolism that shows the worship of fertility and the order of the universe, the aims, and objectives of the semen classic batik are manifested and contained in the names of batik the classics themselves, such as semen rama, semen cuwiri, and semen gendhong; (b) the Parang and Lereng motifs are traditional batik motifs with a line pattern, the name parang is closely related to the existence of Ingkang sinuhun Panembahan Senopati, the founder of the Mataram Kingdom, after the move of the center of government Java from Demak to Mataram, which is the place of “teteki” or the meditation of the first Mataram king who inspired the emergence of batik lerengan or parang as a feature of Mataram ageman which is different from the previous batik; (c) Ceplokan motif means a piece which has the meaning of “power,” the interpretation of symbolism. This is inspired by the concept of power in the four main ornaments and one point in the middle of the ceplok motif, which describes the king’s power over his people and the people who always surround and protect him.